Peningkatan Partisipasi Masyarakat dalam Pengelolaan dan Pemanfaatan Bank Sampah di Kelurahan Batu Gadang - Zahran Mabrukah Tomimi; Ria Ariany; Rozidateno P. Hanida; M. Ichsan Kabullah; Nila Wahyuni (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
Sakinah Waste Bank is one of 175 waste banks that are part of the flagship program of the Padang City Government. The community, as one of the local institutions contributing to increased participation in waste management and utilization, plays a role in reducing waste volume, enhancing environmental awareness, supporting natural resource conservation, improving environmental quality, reducing greenhouse gas emissions, empowering communities, enhancing quality of life, and fostering innovation and creativity among the community. Therefore, it is important to design a strategic agenda in the form of community service based on group activities to strengthen community participation in the management and utilization of waste banks. The approach used is adult education or andragogy, where the instructor acts as a facilitator responsible for facilitating the learning process for students to create a productive and harmonious atmosphere. The results of the community service show that the Sakinah Waste Bank can be utilized not only as a waste collection site but also as a learning space for the community and students in waste utilization and management. To achieve this, the Sakinah Waste Bank can establish closer collaboration with academics and utilize socialization and education as media to enhance the community's understanding and capabilities in participation and empowerment at the Sakinah Waste Bank in Batu Gadang Village, Lubuk Kilangan District, Padang City.